2022
DOI: 10.1038/s41598-022-14571-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of add-on hydroxychloroquine therapy on serum proinflammatory cytokine levels in patients with systemic lupus erythematosus

Abstract: We investigated the effect of hydroxychloroquine (HCQ) as an add-on treatment to immunosuppressants on the expression of proinflammatory cytokines in patients with systemic lupus erythematosus. Serum levels of tumor necrosis factor (TNF)-α, interleukin (IL)-2, IL-6, IL-8, vascular endothelial growth factor (VEGF)-A, monocyte chemotactic protein-1 (MCP-1), macrophage inflammatory protein-1α (MIP-1α), and interleukin 1 receptor antagonist (IL-1ra) were measured immediately before and 3 months after treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…There is conflicting data regarding the effect of HCQ on serum levels of IL-8. While Wakiya et al [ 42 ] showed a negative effect of HCQ, others did not observe any changes [ 43 , 44 ]. Therefore, it remains unresolved to what extent the levels of these cytokine relate to the severity of PE and its phenotypes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting data regarding the effect of HCQ on serum levels of IL-8. While Wakiya et al [ 42 ] showed a negative effect of HCQ, others did not observe any changes [ 43 , 44 ]. Therefore, it remains unresolved to what extent the levels of these cytokine relate to the severity of PE and its phenotypes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hydroxychloroquine (HQC) has been used to treat inflammatory diseases such as SLE, other autoimmune and neoplastic disorders, and metabolic and infectious diseases. When HQC is used in patients with SLE, some signs and symptoms, such as fatigue, skin rashes, joint pain, mouth ulcers, and arthralgia, improve and inhibit the production of inflammatory cytokines [74,75]. In addition, a decrease in aortic stiffness, systemic vascular resistance, and increased elasticity of the large arteries has been noticed; therefore, HQC therapy in SLE exerts a protective effect on coronary artery disease [76,77].…”
Section: Cardiovascular Clinical Assessments In Slementioning
confidence: 99%
“…Several cytokines are implicated in the pathogenesis of AAV, especially IL-6, IL-8, IL-10, IL-17 and TNF-α (tumour necrosis factor alpha) [98] . HCQ has been shown to inhibit the production of IL-6, IL-17 and TNF-α (possibly by inhibiting TLR pathways), in addition to other cytokines like IL-1, IL-2, IL-22, IFN-α (interferon alpha), and IFN-gamma [99,100] .…”
mentioning
confidence: 99%